2011
DOI: 10.1515/jpem.2011.099
|View full text |Cite
|
Sign up to set email alerts
|

Aplasia cutis congenita in surviving co-twin after propylthiouracil exposure in utero

Abstract: Aim: Aplasia cutis congenita (ACC) has been observed after fetal exposure to the antithyroid drug methimazole (MMI), but not reported after propylthiouracil (PTU), the current antithyroid drug of choice during pregnancy. This occurrence has implications for patient information and causal research. Case report: We describe a surviving term co-twin to a mother with hyperthyroidism exposed to PTU from conception to 34 weeks of gestation presenting with ACC at birth. Discussion: The association between PTU exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Furthermore, there has been a reported case of aplasia cutis secondary to PTU exposure during pregnancy and choanal atresia [37]. More recently, a case of aplasia cutis, with skin defect on both flanks, the thighs and the knees, but not on the scalp, was observed in an infant whose mother was exposed to PTU, but not CBZ/MMI in pregnancy [38]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there has been a reported case of aplasia cutis secondary to PTU exposure during pregnancy and choanal atresia [37]. More recently, a case of aplasia cutis, with skin defect on both flanks, the thighs and the knees, but not on the scalp, was observed in an infant whose mother was exposed to PTU, but not CBZ/MMI in pregnancy [38]. …”
Section: Resultsmentioning
confidence: 99%
“…While the in utero exposure to methimazole or propylthiouracil has been associated with aplasia cutis and a number of other congenital defects (Löllgen et al, 2011;Rodriguez-Garcia et al, 2011), an IARC evaluation found inadequate evidence in humans, but limited evidence (in the case of methimazole) and sufficient evidence (in the case of thiouracil, methylthiouracil and propylthiouracil) in experimental animals for carcinogenicity (IARC, 2001;EFSA 2008b).…”
Section: (B) Thyreostatsmentioning
confidence: 99%
“…While the in utero exposure to methimazole or propylthiouracil has been associated with aplasia cutis and a number of other congenital defects (Löllgen et al, 2011;Rodriguez-Garcia et al, 2011), an evaluation by the International Agency for Research on Cancer (IARC) evaluation found inadequate evidence in humans, but limited evidence (in the case of methimazole) and sufficient evidence (in the case of thiouracil, methylthiouracil and propylthiouracil) in experimental animals for carcinogenicity (IARC, 2001;EFSA 2008b).…”
Section: (A) Dioxinsmentioning
confidence: 99%